In the Heart of Secret. Mysterious Murder of the Literary Critique– 2nd part - Tomáš Horváth (Slovenska Literatura, 2007)
The author of the article analyses a classical type of a detective story written by S. S. Van Dine The Greene Murder Case (1928). He uses it as a reference and representative text (as a “textbook of generic grammar “) indicating all the formulated genre, referring also to generic variations in other texts. The description of the characters already in static characteristic introduces elements of iteration, repeating on the successive axis of the text and they form that way a stabile characterisation of a hero. In the focal narrative sequence of solution there are two types of a motif set in confrontation: sujet distribution of enigmatic motives without their sense and correct arrangement of motives (their sense in encomia of a secret solution). The detective has to deduce it from enigmaticly distributed data through his own mechanism of judgement. In the Van Dine novel a holistic type of problem shooting operates: one introduced hypothesis explains “in one move” all morphemes of the secret and that is why it is correct. (If whoever else murders except of the right murder, it will not be necessary to let the lights switched on in all the rooms, the woman, a murder, would not be found in the lit up room shot in front of the mirror just because to be able to shoot herself etc.) We show strategies of the text through which a model reader is deceived to construct incorrect possible world of the own hypothesis and also to construct an incorrect possible world in the hypothesis excluding a real perpetrator from the list of suspicious persons. As an illustration we use and example from famous Holmes´ solution concerning a dog in the short story Silver Blaze and we model process of abduction and entymematic inference that produces the resolution: the detective looks up in the cultural encyclopaedia hidden premise (that a guarding dog barks or attacks an invader) and he connects it with actual indicia (the dog did not respond the right way), due to it he brings hypothesis: the dog must know the perpetrator.